Secure Data Management 6th VLDB Workshop, SDM 2009, Lyon, France, August 28, 2009, Proceedings - Jonker, Willem; Petkovic, Milan (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the 6th VLDB Workshop on Secure Data Management, SDM 2009, held in Lyon, France, on August 28, 2009, in conjunction with VLDB 2009. The 10 revised full papers presented were carefully reviewed and selected from 24 submissions for publication in the book. The topics in this volume range from traditional ones, such as access control and general database security, via provacy protection to new research directions, such as cryptographically enforded access control. The papers are organized in topical sections on database security, access control, and privacy protection.